Component gradient solid electrolyte and preparation method thereof
By using component gradient solid electrolytes in high-voltage batteries and using multi-material 3D printing technology to form an integrated electrolyte membrane, the lithium metal dendrite problem and battery compatibility problems are solved, and the battery performance with high energy density and long life is achieved.
Patent Information
- Application Number
- CN202411343649.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
In high-voltage battery systems, traditional liquid electrolytes lead to lithium metal dendrite problems and reduced battery cycle life, and it is difficult to achieve good interface compatibility between the positive and negative electrodes at the same time.
The composition gradient solid electrolyte is adopted, and the high-voltage positive electrode compatible solid electrolyte and the lithium metal negative electrode compatible solid electrolyte are formed through the multi-material 3D printing technology of the mixed printing nozzle to form an integrated composition uniform transition film to ensure stability and compatibility at high voltages.
It realizes a high-energy density battery system, reduces the internal interface resistance of the electrolyte membrane, improves the cycle life and safety of the battery, and has the advantages of high design freedom and low cost.
Smart Images

Figure CN119253046A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid-state lithium metal batteries, and in particular to a composition gradient solid-state electrolyte and a preparation method thereof. Background Art
[0002] The rapid development of mobile electronic devices and electric vehicles has put forward higher requirements on the energy density of batteries. An effective way to achieve a significant increase in battery energy density is to combine high-voltage positive electrode materials (lithium cobalt oxide, ternary materials, etc.) with high-specific capacity lithium metal negative electrodes. In this case, the operating voltage window of the battery is expanded, and the overall energy density can be increased by 20-50%. However, in the above-mentioned high-voltage battery system, when the electrolyte still uses traditional carbonate liquid electrolytes, the negative electrode lithium metal has serious dendrite problems, and the lithium metal dendrites will pierce the diaphragm, causing the battery to short-circuit. In addition, the above-mentioned liquid electrolyte has a narrow electrochemical window, and the electrolyte undergoes continuous oxidation and decomposition on the surface of the high-voltage positive electrode during the cycle, which greatly reduces the cycle life of the battery.
[0003] Some solid electrolytes will not decompose in a voltage window above 5V, such as Li 10 G 2 S 12 , Li 3 PS 4 , Li 4 S N 4 , Li 7 La 3 Zr 2 O 12 and lithium phosphorus oxynitride (LiPON). Therefore, one strategy to solve the above problems is to use solid electrolytes instead of traditional liquid electrolytes, that is, to build a solid-state high-voltage battery system. In addition, compared with carbonate electrolytes, most solid electrolytes are inherently non-flammable, which can improve the safety of the battery, and solid electrolytes have high mechanical strength and can effectively inhibit the growth of lithium dendrites.
[0004] At present, there is an urgent need to provide a solid electrolyte system that can meet the requirements of both the positive and negative electrodes, that is, to achieve good interface compatibility with both the lithium metal negative electrode and the high-voltage positive electrode.
[0005] The information in this background technology section is only intended to enhance the understanding of the overall background of the application and should not be construed as an admission or any form of suggestion that the information constitutes the prior art already known to a person of ordinary skill in the art. Summary of the invention
[0006] In order to solve the above problems, the present application provides a composition gradient solid electrolyte and a preparation method thereof. The composition gradient solid electrolyte of the present application is composed of two solid electrolytes of different components, namely a high-voltage positive electrode compatible solid electrolyte and a lithium metal negative electrode compatible solid electrolyte. The two solid electrolytes are not simply physically mixed or physically superimposed together, but form an integrated solid electrolyte membrane with uniform composition transition. One side of the obtained composition gradient solid electrolyte membrane is compatible with the high-voltage positive electrode, is stable under high voltage, and does not undergo oxidative decomposition. The other side is compatible with the lithium metal negative electrode, can fit closely with the lithium metal interface, and inhibit the growth of lithium dendrites.
[0007] The multi-material 3D printing technology based on the hybrid printing nozzle dynamically and in real time changes the feed speed of two independent printing nozzles, thereby controlling the mixing ratio of the two components and achieving a uniform transition of the composition of the electrolyte membrane from one layer to the other.
[0008] In some embodiments of the present application, a method for preparing a composition gradient solid electrolyte is provided, comprising the following steps:
[0009] S1: Preparation of high voltage cathode compatible solid electrolyte ink:
[0010] Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and lithium salt are sequentially added to an organic solvent, and magnetically stirred for a certain period of time under heating conditions to obtain a uniform high-voltage cathode-compatible solid electrolyte ink;
[0011] S2: Preparation of Li-metal Anode Compatible Solid Electrolyte Ink:
[0012] The polyethylene oxide (PEO) and lithium salt are dissolved in an organic solvent and stirred for a certain period of time under heating conditions to obtain a lithium metal compatible solid electrolyte ink;
[0013] S3: The multi-material 3D printing technology based on the hybrid printing nozzle realizes the printing of composition gradient solid electrolyte. In the feeding module, the high-voltage compatible solid electrolyte and the lithium metal compatible solid electrolyte are respectively loaded into the printing barrel I and the printing barrel II, and are fully mixed through the mixer, and then extruded from the nozzle and printed onto the substrate to form a solid electrolyte with a material composition gradient from bottom to top;
[0014] S4: Solvent removal and curing:
[0015] The printed composition-gradient solid electrolyte is vacuum heated to remove the solvent and solidify.
[0016] In some embodiments of the present application, in step S1, the lithium salt is one or more combinations of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluorophosphate.
[0017] In some embodiments of the present application, the organic solvent in steps S1 and S2 is polydimethylformamide (DMF).
[0018] In some embodiments of the present application, the weight ratio of PVDF-HFP to lithium salt is 1:1 to 10:1.
[0019] In some embodiments of the present application, in step S1, the heating temperature is 40-60°C and the heating time is 4-12h.
[0020] In some embodiments of the present application, in step S2, the lithium salt is one or more combinations of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluorophosphate.
[0021] In some embodiments of the present application, the ratio of PEO to lithium salt is as follows: + The molar ratio is determined at 10:1 to 40:1.
[0022] In some embodiments of the present application, in step S2, the heating temperature is 40-60°C and the heating time is 4-12h.
[0023] In some embodiments of the present application, in step S3, the size specification of the printing cartridge I is a 1-60 mL syringe.
[0024] In some embodiments of the present application, in step S3, the feeding speed of the printing cylinder I is 0-1 mL / min.
[0025] In some embodiments of the present application, in step S3, the size specification of the printing cartridge II is a 1-60 ml syringe.
[0026] In some embodiments of the present application, in step S3, the feeding speed of the printing cartridge II is 0-1 mL / min.
[0027] In some embodiments of the present application, in order to achieve a gradient change in the composition of the electrolyte, in step S3, the feeding speeds of the printing cartridge I and the printing cartridge II are inconsistent, and the sum of the two is maintained at 1 mL / min.
[0028] In some embodiments of the present application, in step S3, the printing speed is 5-20 mm / s.
[0029] In some embodiments of the present application, the feed rate of print cartridge I is gradually increased from 0 mL / min to 1 mL / min. On the contrary, the feed rate of print cartridge II is gradually increased from 1 mL / min to 0 mL / min. The sum of the feed rates of the two cartridges is maintained at 1 mL / min.
[0030] In some embodiments of the present application, in step S4, the vacuum heating temperature is 60-90° C., and the heating time is 24-48 hours.
[0031] In some embodiments of the present application, the heating device in step S4 is an oven.
[0032] In another embodiment of the present application, a composition gradient solid electrolyte is also provided, which is prepared by the above preparation method.
[0033] In some embodiments of the present application, the composition gradient solid electrolyte has a solid electrolyte interface on the positive electrode side of 100% PVDF-HFP + 0% PEO-based polymer electrolyte, which avoids oxidative decomposition under high voltage conditions and ensures compatibility with the high-voltage positive electrode; the solid electrolyte interface on the negative electrode side is 0% PVDF-HFP + 100% PEO-based polymer electrolyte, which fits tightly with the lithium metal negative electrode and inhibits the growth of lithium dendrites.
[0034] In some embodiments of the present application, the electrolyte composition gradient changes between the positive electrode side solid electrolyte interface and the negative electrode side solid electrolyte interface.
[0035] The technical solution of the present application has at least the following advantages and beneficial effects:
[0036] 1. The composition gradient solid electrolyte proposed in this application is composed of two electrolyte components, and the two components change continuously in the thickness direction of the electrolyte membrane, with an integrated structure, rather than the traditional two independent component electrolyte membranes simply stacked together. This integrated composition gradient electrolyte membrane greatly reduces the interface resistance inside the electrolyte membrane.
[0037] 2. The composition gradient electrolyte membrane proposed in this application has both high-voltage positive electrode compatibility and lithium metal negative electrode compatibility.
[0038] 3. The composition gradient solid electrolyte proposed in this application can be used in a high-voltage battery system consisting of a high-voltage positive electrode and a lithium metal negative electrode to achieve a high battery energy density.
[0039] 4. The method for preparing composition gradient solid electrolyte proposed in this application is a multi-material 3D printing technology based on a hybrid printing nozzle, which has the advantages of high design freedom, high material utilization, low cost and easy mass production. Solid electrolyte films of different thicknesses, sizes and components can be customized according to needs.
[0040] 5. The preparation method of the present application can realize the preparation of a high ionic conductivity solid electrolyte membrane with uniform composition transition and high compatibility with positive and negative electrodes, and has important practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The drawings in the specification, which constitute a part of the present application, are used to provide further understanding of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute improper limitations on the present application.
[0042] Figure 1 This is a schematic diagram of printing a composition-gradient solid electrolyte in some embodiments of the present application.
[0043] Figure 2 This is a schematic diagram of the printed composition gradient solid electrolyte in some embodiments of the present application. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solutions and advantages of the present application more clearly understood, the present application is described in detail in some embodiments of the present application in combination with the embodiments and drawings. The schematic implementation methods of the present application and their description are only used to explain the present application and are not intended to limit the present application.
[0045] In the present application, the terms "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, article or device. In the absence of further restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, article or device including the element.
[0046] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design scheme described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0047] Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0048] The inventors found in their research that among polymer-based solid electrolytes, polyethylene oxide (PEO) solid electrolytes exhibit good interfacial compatibility with lithium metal anodes. However, PEO electrolytes are easily x Co y Mn z O 2(X + Y + Z = 1, 0.5 < X < 1) Cathode side decomposition limits its application in high-voltage cathode systems; Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) polymer can match with high-voltage cathode materials due to its excellent antioxidant ability, good film-forming performance and high ionic conductivity. However, there is poor physical contact between the rigid PVDF-HFP electrolyte and lithium metal, and even side reactions occur between them. A single solid electrolyte system has always been difficult to simultaneously meet the high-voltage stability of the cathode and good lithium metal compatibility.
[0049] Moreover, in the existing battery assembly process, two electrolyte membranes are usually stacked together. The compositions of the two electrolyte membranes are completely different, and an obvious physical interface will be generated in the middle, which will increase the interfacial impedance of ion conduction and thus affect the battery performance.
[0050] In some embodiments of the present application, a method for preparing a composition gradient solid electrolyte is provided, including the following steps:
[0051] S1: Prepare a high-voltage cathode compatible solid electrolyte ink:
[0052] Add poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and lithium salt into an organic solvent in sequence, and magnetically stir for a certain time under heating conditions to obtain a uniform high-voltage cathode compatible solid electrolyte ink;
[0053] S2: Prepare a lithium metal anode compatible solid electrolyte ink:
[0054] Dissolve polyethylene oxide (PEO) and lithium salt in an organic solvent, and stir for a certain time under heating conditions to obtain a lithium metal compatible solid electrolyte ink;
[0055] S3: Implement 3D printing of the composition gradient solid electrolyte based on the multi-material 3D printing technology of a hybrid print head. In the feeding module, load the high-voltage cathode compatible solid electrolyte and the lithium metal anode compatible solid electrolyte into the print cartridge I and the print cartridge II respectively, mix them充分 through a mixer, and then extrude from the nozzle and print onto the substrate to form a solid electrolyte with a gradient change in material composition from bottom to top;
[0056] S4: Remove the solvent and cure:
[0057] Vacuum heat the printed composition gradient solid electrolyte to remove the solvent and cure.
[0058] In some embodiments of the present application, in step S1, the lithium salt is one or a combination of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluorophosphate.
[0059] In some embodiments of the present application, the organic solvent in steps S1 and S2 is polydimethylformamide (DMF).
[0060] In some embodiments of the present application, the weight ratio of PVDF-HFP to lithium salt is 1:1 to 10:1.
[0061] In some embodiments of the present application, in step S1, the heating temperature is 40-60°C and the heating time is 4-12h.
[0062] In some embodiments of the present application, in step S2, the lithium salt is one or more combinations of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluorophosphate.
[0063] In some embodiments of the present application, the ratio of PEO to lithium salt is as follows: + The molar ratio is determined at 10:1 to 40:1.
[0064] In some embodiments of the present application, in step S2, the heating temperature is 40-60°C and the heating time is 4-12h.
[0065] In some embodiments of the present application, in step S3, the size specification of the printing cartridge I is a 1-60 mL syringe.
[0066] In some embodiments of the present application, in step S3, the feeding speed of the printing cylinder I is 0-1 mL / min.
[0067] In some embodiments of the present application, in step S3, the size specification of the printing cartridge II is a 1-60 ml syringe.
[0068] In some embodiments of the present application, in step S3, the feeding speed of the printing cartridge II is 0-1 mL / min.
[0069] In some embodiments of the present application, in order to achieve a gradient change in the composition of the electrolyte, in step S3, the feeding speeds of the printing cartridge I and the printing cartridge II are inconsistent, and the sum of the two is maintained at 1 mL / min.
[0070] In some embodiments of the present application, high-voltage positive electrode compatible electrolyte ink and lithium metal negative electrode compatible electrolyte ink are extruded from printing cartridge I and printing cartridge II, respectively, and then mixed and evenly mixed by the printing nozzle, and printed into an electrolyte membrane on the printing substrate by the nozzle base.
[0071] In some embodiments of the present application, the hybrid printing nozzle is provided with spiral blades to facilitate the mixed printing of inks.
[0072] In some embodiments of the present application, in step S3, the printing speed is 5-20 mm / s.
[0073] In some embodiments of the present application, the feed rate of print cartridge I is gradually increased from 0 mL / min to 1 mL / min. On the contrary, the feed rate of print cartridge II is gradually increased from 1 mL / min to 0 mL / min. The sum of the feed rates of the two cartridges is maintained at 1 mL / min.
[0074] In some embodiments of the present application, in step S4, the vacuum heating temperature is 60-90° C., and the heating time is 24-48 hours.
[0075] In some embodiments of the present application, the heating device in step S4 is an oven.
[0076] In another embodiment of the present application, a composition gradient solid electrolyte is also provided, which is prepared by the above preparation method.
[0077] In some embodiments of the present application, the composition gradient solid electrolyte has a solid electrolyte interface on the positive electrode side of 100% PVDF-HFP + 0% PEO-based polymer electrolyte, which avoids oxidative decomposition under high voltage conditions and ensures compatibility with the high-voltage positive electrode; the solid electrolyte interface on the negative electrode side is 0% PVDF-HFP + 100% PEO-based polymer electrolyte, which fits tightly with the lithium metal negative electrode and inhibits the growth of lithium dendrites.
[0078] In some embodiments of the present application, the electrolyte composition gradient changes between the positive electrode side solid electrolyte interface and the negative electrode side solid electrolyte interface.
[0079] In some embodiments of the present application, a composition gradient solid electrolyte and a preparation method thereof include the following steps:
[0080] S1: Preparation of high voltage cathode compatible solid electrolyte ink:
[0081] Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added to polydimethylformamide (DMF) in a mass ratio of 5:1, and magnetically stirred at 50°C for 6 hours to obtain a uniform high-voltage cathode-compatible solid electrolyte ink; the weight ratio of PVDF-HFP to LiTFSI was 5:1.
[0082] S2: Preparation of lithium metal anode compatible solid electrolyte ink: polyethylene oxide (PEO) and LiTFSI were dissolved in DMF, and the ratio of PEO to LiTFSI was 1:1. + The molar ratio was determined to be 20:1, and magnetic stirring was performed at 50°C for 6 h to obtain a lithium metal compatible solid electrolyte ink.
[0083] S3: Multi-material 3D printing technology based on hybrid printing nozzle realizes composition gradient solid electrolyte printing:
[0084] In the feeding module, two electrolyte inks, namely, high-voltage compatible solid electrolyte and lithium metal compatible solid electrolyte, are loaded into printing cartridge I and printing cartridge II, respectively.
[0085] The size of the printing barrel I and the printing barrel II is a 10mL syringe. The two printing inks are fully mixed after passing through the passive mixer, extruded from the nozzle, and further printed onto the substrate. By dynamically changing the feeding speed of the two feeding barrels, the gradient change of the material composition of the solid electrolyte membrane from bottom to top during the printing process is achieved.
[0086] In the specific implementation, the feeding speed of barrel I is gradually increased from 0 mL / min to 1 mL / min. On the contrary, the feeding speed of barrel II is gradually increased from 1 mL / min to 0 mL / min. The sum of the feeding speeds of the two barrels is maintained at 1 mL / min. The printing speed is 10 mm / s. This technology can ensure printing efficiency and printing accuracy at the same time, and is suitable for large-scale and batch production.
[0087] S4: Removal of solvent and curing: The printed composition gradient solid electrolyte membrane is transferred to an oven and heated at 60° C. under vacuum for 24 h to remove the solvent.
[0088] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the protection scope of the claims.
Claims
1. A method for preparing a composition gradient solid electrolyte, characterized in that: The following steps are involved: S1: Preparation of high voltage cathode compatible solid electrolyte ink: Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and lithium salt are sequentially added to an organic solvent, and magnetically stirred for a certain period of time under heating conditions to obtain a uniform high-voltage cathode-compatible solid electrolyte ink; S2: Preparation of Li-metal Anode Compatible Solid Electrolyte Ink: The polyethylene oxide (PEO) and lithium salt are dissolved in an organic solvent and stirred for a certain period of time under heating conditions to obtain a lithium metal compatible solid electrolyte ink; S3: The multi-material 3D printing technology based on the hybrid printing nozzle realizes the printing of composition gradient solid electrolyte. In the feeding module, the high-voltage compatible solid electrolyte and the lithium metal compatible solid electrolyte are respectively loaded into the printing barrel I and the printing barrel II, and are fully mixed through the mixer, and then extruded from the nozzle and printed onto the substrate. By dynamically changing the feeding speed of the printing barrel I and the printing barrel II, a solid electrolyte with a material composition gradient from bottom to top is formed; S4: Solvent removal and curing: The printed composition-gradient solid electrolyte is vacuum heated to remove the solvent and solidify.
2. The method for preparing a composition gradient solid electrolyte according to claim 1, characterized in that: In step S1, the lithium salt is one or more combinations of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluorophosphate; the weight ratio of PVDF-HFP to the lithium salt is 1:1 to 10:1; the organic solvent in steps S1 and S2 is polydimethylformamide (DMF).
3. The method for preparing a composition gradient solid electrolyte according to claim 1, characterized in that: In step S1, the heating temperature is 40-60°C and the heating time is 4-12h; in step S2, the heating temperature is 40-60°C and the heating time is 4-12h.
4. The method for preparing a composition gradient solid electrolyte according to claim 1, characterized in that: In step S2, the lithium salt is one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluorophosphate; the ratio of PEO to lithium salt is based on the ratio of ethylene oxide group EO to Li + The molar ratio is determined at 10:1 to 40:
1.
5. The method for preparing a composition gradient solid electrolyte according to claim 1, characterized in that: In step S3, the size specifications of the printing cartridge I and the printing cartridge II are both 1-60 mL syringes; in step S3, the feeding speed of the printing cartridge I and the printing cartridge II is 0-1 mL / min.
6. The method for preparing a composition gradient solid electrolyte according to claim 1, characterized in that: In step S3, the feeding speeds of printing cartridge I and printing cartridge II are inconsistent, and the sum of the two is maintained at 1 mL / min; in step S3, the printing speed is 5-20 mm / s.
7. The method for preparing a composition gradient solid electrolyte according to claim 1, characterized in that: The feed rate of print cartridge I gradually increases from 0 mL / min to 1 mL / min; conversely, the feed rate of print cartridge II gradually increases from 1 mL / min to 0 mL / min; the sum of the feed rates of the two cartridges remains at 1 mL / min.
8. The method for preparing a composition gradient solid electrolyte according to claim 1, characterized in that: In step S4, the vacuum heating temperature is 60-90° C., and the heating time is 24-48 hours; the heating device in step S4 is an oven.
9. A composition gradient solid electrolyte, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A composition gradient solid electrolyte according to claim 9, characterized in that: The composition gradient solid electrolyte has a positive electrode side solid electrolyte interface of 100% PVDF-HFP+0% PEO-based polymer electrolyte, and a negative electrode side solid electrolyte interface of 0% PVDF-HFP+100% PEO-based polymer electrolyte, which is bonded to the lithium metal negative electrode.
Citation Information
Cited By
Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device
CN122224962A
